Supercritical water convection loop control system - Boriskin, V.N.; Momot, V.A.; Romanovsky, S.K.; Savchenko, A.N.; Solodovnikov, V.I.; Shelepko, S.V. (Вопросы атомной науки и техники, 2014)
The Convection Loop control system for research of water parameters in supercritical and "nearby" critical state is considered. Results of experiments are presented.